2015
DOI: 10.1155/2015/717509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chromosome 17 miRNAs and Their Importance in Medulloblastomas

Abstract: MicroRNAs (miRNAs) are small sequences of nucleotides that regulate posttranscriptionally gene expression. In recent years they have been recognized as very important general regulators of proliferation, differentiation, adhesion, cell death, and others. In some cases, the characteristic presence of miRNAs reflects some of the cellular pathways that may be altered. Particularly medulloblastomas (MB) represent entities that undergo almost characteristic alterations of chromosome 17: from loss of discrete fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For example, 8 SDE-circRNA were all derived from chromosome 17, with nearly half of the genes with upregulated expression (46%, 6 out of 13) distributed on this chromosome ( Figure 1 B). Given that chromosome 17 is associated with many cancers [ 23 , 24 , 25 ], therefore, it is also worth exploring the circRNA related to cancer from chromosome 17.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 8 SDE-circRNA were all derived from chromosome 17, with nearly half of the genes with upregulated expression (46%, 6 out of 13) distributed on this chromosome ( Figure 1 B). Given that chromosome 17 is associated with many cancers [ 23 , 24 , 25 ], therefore, it is also worth exploring the circRNA related to cancer from chromosome 17.…”
Section: Resultsmentioning
confidence: 99%
“…miR-424 is a breast cancer suppressor, and loss of miR-424 expression can enhance resistance to chemotherapy ( 23 , 24 ). Thus, they not only could be specific diagnostic markers for certain malignant tumors and hereditary diseases, but also indicators of invasion, migration, drug resistance or prognosis of malignant tumors ( 26 , 27 ). A previous study analyzed the results of a glioma-related GeneChip and found that there are ~22 differentially expressed miRNAs, and that some miRNAs promote the proliferation of GBM cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies have demonstrated that several micro-RNAs (miRNAs) are associated with the invasion process in gliomas and other tumor cells. 10,11 MicroRNAs are highly conserved endogenous small noncoding RNAs, which contain 19 to 21 nucleotides and suppress gene expression posttranscriptionally by targeting the 3 0 untranslated regions of messenger RNAs (mRNAs). 12 MicroRNAs have gained more attention in regulating molecular pathogenesis of cancer recently, because each miRNA could suppress hundreds of targets that may play various roles in different tissues or cells.…”
Section: Introductionmentioning
confidence: 99%